(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The selection of educational technologies for the formation of base compensations in students, the subject of the calendar of the teacher of educational science determines the base compensations established for this class in the plan. After that, the method of passing the lesson, taking into account the subject that needs to be studied and the compensations that will be formed, is selected. Teachers create a favorable environment for the good organization of the lesson process. Students are allowed to exchange ideas (information) among themselves. They will discuss and solve the issues waiting for their solution in harmony. They will find a collaborative solution to get out of the situation. They will demonstrate their knowledge to each other on the basis of the information they receive. In this article, opinions and comments are made about the factors that influence the formation of social compensation in students. The article is devoted to the topical issue of formation and development of information competence among school children. In determining the concept of" information competence", the analysis of many influential scientists-educators is summarized. The article presents the components of the category" information competence"